Not-yet-designed multilayer Nb/HA/MWCNT-Au/Se/AuNPs and NbO2/HA/GO/Se biocomposites coated Ti6Al7Nb implant - Rafieerad, Ali Reza; Bushroa, Abdul Razak; Banihashemian, S.M.; Amiri, Ahmad (Elsevier, 2018)
Increased commercial demands of appropriate bone materials, smart multilayer biocomposites named niobium/hydroxyapatite/multiwall carbon nanotube hybrid gold/selenium/gold nanoparticles (Nb/HA/MWCNT-Au/Se/AuNPs) and niobium oxide/hydroxyapatite/graphene oxide/selenium (NbO2/HA/GO/Se) support Ti-6Al-7Nb implant alloy (Ti67IMP). Adhesion strength of primary as-deposited films was assessed by micro-scratch nanomaterial analysis. The microstructure, phase and elemental features of developed large-surface-area composites were characterized via FESEM, TEM/HRTEM, XPS, XRD/GIXRD, Raman and FT-IR techniques. Besides, in-vitro bioactivity study of reinforced Ti67IMP in simulated body fluid (SBF) media followed to evaluate the enhanced potential of bone-like apatite layer formation on treated surfaces comparatively. The designed multilayer biofilm-Ti67IMP systems may contribute to facilitate low-risk bone regeneration with antibacterial and drug delivery potential and long-term mechanical satisfaction.